Home-Based Learning Activities (H-BLA) In Teaching Physics Topics For Elementary School Students - Candia, Robert; Glomar , Gladys; Joven , Camele; Lasala, Nestor Jr (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study developed and validated Home-Based Learning Activities (H-BLA) for teaching Physics inspired by the identified Most Essential Learning Competencies (MELCs) by the Department of Education (DepEd). Acknowledging the significance of adaptive and suitable learning materials. Methodology: The researchers employed the descriptive-developmental method to create and assess the developed home-based learning activities. The Learning Resources Management and Development System (LRMDS) evaluation tool of the Department of Education (DepEd) for printed materials is used and experts agreed that the developed H-BLA met the standards for printed learning materials. Main Findings: The findings revealed that the level of validity of H-BLA in terms of content, format, accuracy, and up-to-datedness of information of H-BLA was very much acceptable as validated by the experts supported by the result of factors 1, 2, and 4 being very satisfactory. However, the presentation and organization of H-BLA got a